Ocenka funkcii ravnovesija u junych tjaželoatletov v praktike trenirovocnogo mezocikla - Beljaev, V. S.; Matveev, Ju. A.; Tusher, Ju. L.; Chernogorov, D. N. (Vestnik Moskovskogo gorodskogo pedagogiceskogo universiteta. Serija «Estestvennye nauki», 2015)
Possibility of use of static motive and cognitive tests on a stabilometry method for an assessment of statokinetic stability and function of balance at young weight-lifters with the purpose of increase the level of their coordination preparation is substantiated in the article.